RESHAPING THE VALUE PROPOSITION: STRATEGIC RESPONSES OF LANGUAGE COURSE PROVIDERS TO THE AI REVOLUTION - Tjahyanto, Mario Christian Noer; Yenny, Hartanto (Jurnal Bisnis Terapan, 2026)
The rapid proliferation of Generative Artificial Intelligence (GenAI) has catalyzed a fundamental shift in the education sector, specifically disrupting the traditional business model of Language Course Providers (LCPs). As AI-driven tools provide high-quality translation and personalized tutoring at near-zero marginal costs, traditional language services are experiencing rapid commoditization. This research explores how LCPs can reshape their value propositions to maintain strategic relevance and financial sustainability. Utilizing a qualitative conceptual research design, the study applies the Value Proposition Canvas (VPC) and Disruptive Innovation frameworks to analyze the gap between automated AI capabilities and human-centric pedagogical needs. Empirical evidence from a case study reveals a staggering 80% decrease in document translation requests and a 60% decline in course registrations, signaling a "tipping point" for the industry. The findings indicate that while AI excels at linguistic accuracy, it lacks the capacity for intercultural mediation, ethical judgment, and institutional trust. Consequently, the study proposes a strategic transition from a "content-provider" model to a "Communication-Consultancy" framework. This "Cyborg" pedagogy integrates AI for repetitive rote learning while focusing human expertise on high-stakes specialized training and AI literacy. Managerial implications emphasize the necessity for staff upskilling and the repositioning of LCPs as "Verification Hubs" in a digital era. By adopting these strategic responses, LCPs can pivot from being perceived as administrative cost centers to becoming indispensable drivers of global communication.